Pilot Scale Production of Irradiated Natural Rubber Latex and its Dipping Products - M. Utama; M. Suhartini; Herwinarni Herwinarni; Siswanto Siswanto; S. Yoharmus; H. Sundaru; H.M. Halik; Prayitno Prayitno; H.M. Muklis; S. Ruslim (Atom Indonesia, 2005)
One hundred and fifty kg natural rubber latex (NRL) before and after concentration were added with 3 phr (part hundred ratio of rubber) normal butyl acrylate, then the mixture were irradiated at 25 kGy by gamma rays of 60Co in pilot scale. The irradiated natural rubber latex (INRL) were then being to use for producing rubber products such as condom, surgical gloves, and spygmomanometer in factory scale. The quality of INRL and rubber products such as : total solid content (TSC), dry rubber content (DRC), KOH, VFA and MST number, tensile strength, modulus, elongation at break, extractable protein content, and response against Type I allergy etc. were evaluated. The economic aspect for producing INRL by means of Gamma Irradiator (GI) and Electron Beam Machine (EBM) such as payback period (PP), net present value (NPV) and internal rate return (IRR) were calculated. The results showed that the latex properties of INRL such as DRC, TSC, KOH, VFA, and MST number are not only found to the requirement of the ISO 2004 standard but also the latex has low protein, lipid, and carbohydrate content. The physical and mechanical properties (tensile strength, modulus, and elongation at break) of rubber dipping products such as condom, gloves, and sphygmomanometer are not only found to the requirement of ISO 4074, ISO 10282, and ANSI/AAMI SP-1994 standards, but also the allergic response tested clinical latex-sensitive protein allergen by ELISA test on gloves, and by SPT test on condom are found to be negative. It indicates that production of INRL or PVNRL or RVNRL by EBM 250 keV/10 mA, was more cheap than by using gamma γ irradiator 200 kCi, or sulfur vulcanization. The value of PBP (payback period) was 2,1 years, NPV (net present value) was 4,250 US $, PI (profitability index) 1,06 and IRR (internal rate of returns) was 25,0%.